Comércio ambulante: negociações e resistências cotidianas no centro de João Pessoa – PB - Silva, Mylena Serafim da (2021)
To interpret the various forms of informal work in contemporary times is also to seek to understand the interactions in contemporary society. This writing aims to demonstrate how the street trade at the collective level reacts, whether with negotiations or resistance, in the face of its constant prohibition. Being an ethnographic design research, the clipping was given to a specific field that is the city center of João Pessoa-PB. The methodology used to carry out the research, in addition to on-site observation and interviews, was the resource of online research, documentary analysis and bibliographic survey on the proposed theme. Street or street commerce is as traditional as it is current, changing as the buying and selling relationships also become modernized, and while they continue to be the basis of the capitalist society we experience. As a result of the research, it was observed the presentation of a changeable permanence of the street trade that, even being an unregulated activity and so- called illegal in the face of city legislation, continues to act, even if it is under other configurations. Thus, it is considered how much negotiations and resistanceare objects of struggle to have the right to work and the importance of these strategies for the performance of the ambulantes and the street walkers in the city's commerce.